A new combination in Smyrnium (Apiaceae) - Stinca, Adriano; Pignatti, Sandro (Phytotaxa, 2016)
Recently, Raimondo et al. (2015) described a new species for Sicily and Creta, i.e. Smyrnium dimartinoi Raimondo, Mazzola & Spadaro (2015: 138). This taxon is closely related morphologically and ecologically to the aggregate of S. perfoliatum Linnaeus (1753: 262), in which two subspecies are usually recognized (cf. Hartvig 1986, Conti et al. 2005, Reduron 2008, Hand 2011): S. perfoliatum subsp. perfoliatum and S. perfoliatum subsp. rotundifolium (Miller 1768: without pagination) Bonnier & Layens (1894: 135).